Long-Term Lung Function and Exercise Capacity in Postinfectious chILD - Sisman, Yagmur (Pediatr Allergy Immunol Pulmonol, 2019)
Background: Severe postinfectious diffuse pulmonary disease may clinically mimic other entities of children's interstitial lung disease and is clinically challenging comprising various disease severities despite treatment. Long-term lung function trend and physical capacity in children with postinfectious diffuse pulmonary disease are rarely reported. We investigated trends in pulmonary function by long-term follow-up and assessed physical capacity in such patients. Methods: We performed a descriptive, single-center follow-up study in children with biopsy-verified postinfectious diffuse pulmonary disease. Patients with completed primary treatment course were eligible for follow-up, including pulmonary function and exercise (VO(2peak)) testing. Results: Thirty patients with postinfectious diffuse pulmonary disease were identified and included. Median (range) age at diagnose was 27.5 (2–172) months after a mean lag time of 23 months. H. influenzae and rhinovirus were the most frequent pathogens. Fifteen patients were available for follow-up after mean (range) 7.6 (2–15) years of treatment completion. Lung clearance index (LCI(2.5)), forced expiratory volume in 1 second (FEV(1)), and bronchodilator responsiveness were abnormal in 80%, 53%, and 44%, respectively. Diffusion capacity for monoxide was abnormal in 7% and total lung capacity in 33%. Only 8% demonstrated low VO(2peak), while 40% reported difficulties during physical exertion. Longitudinal data on spirometry (n = 14) remained unchanged from end of treatment throughout follow-up. A significant association was found between zLCI(2.5) and zFEV(1) (multiple linear regression; r(2) = 0.61; P = 0.0003). Conclusion: Postinfectious diffuse pulmonary disease in children carries a varying degree of chronic pulmonary impairment with onset of symptoms in the first months of life and a typical considerable lag time before diagnosis. Follow-up several years after the initial injury demonstrated moderate-to-severe peripheral airway impairment although no further lung function decline was found years after completion of treatment. Despite acceptable VO(2peak), a considerable proportion struggled during heavy exercise.